The Influence of Workload on the Performance of Banjarmasin City Land Office Employees Through Motivational Mediation - Meiske Claudia; Al Amin, Achmad Rizal (HM Publisher, 2024)
Workload is an important factor that can influence employee performance. Excessive workload can cause stress and fatigue, which can reduce employee performance. On the other hand, motivation can be a determining factor in improving employee performance. High motivation can encourage employees to work harder and be more productive. This research aims to determine and analyze the effect of workload on performance by mediating motivation among Banjarmasin City Land Office Employees. This research method uses a questionnaire of 40 Banjarmasin City Land Office employees as samples and the sampling technique used is purposive sampling with judgment sampling type. Data analysis uses the SEM-PLS (Structural Equation Modeling - Partial Least Square) method which is processed with the SmartPLS Program. The results of this research conclude that the workload variable has a significant negative effect on the performance variable, the workload variable has a significant positive effect on the motivation variable, the motivation variable has a significant positive effect on the performance variable, and the workload variable has a significant positive effect on the performance variable with the mediation of the motivation variable.